“Evaluación de la Estabilidad de Antocianinas durante el Almacenamiento de Zanahoria Púrpura (Daucus carota)” - Valle Colchao y Cols., Manuel E (2019)
Research was intended evaluate Stability of Anthocyanins in the Storge of Carrot Purple (Daucus carota), Indigo winter, comes from of Instituto Nacional de Innovación Agraria (INIA) – Estación Experimental Agraria Donoso Huaral. It was harvested in physiological maturity, later it went to Composition and Analysis Agroindustrial Products Laboratory where it was selected, classified uniformly and were packed in groups of 3; where two of them were of Low-Density Polyethylene and Low-Density Polypropylene and other one without packing; then they were stored in 3 different temperatures; Environment, 5º C and 10º C. Variable dependent on study evaluated Anthocyanin Conservation Rate. For a period of storage of 11 days. The Research compared the best results of the packed samples; the carrot purple packed in Low-Density Polyethylene and Stored to 5º C, which preserved better the Anthocyanin (97.03 %). In compares of one not packed and stored to Temperature Environment, there was obtained conservations 94.03 %.